1975
DOI: 10.1093/brain/98.4.595
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Kuru in the Spider Monkey

Abstract: The brains of 10 spider monkeys inoculated intracerebrally with brain suspension from kuru patients have been studied histologically and ultrastructurally. The animals were killed by perfusion of fixative from four to forty-one weeks after inoculation, when healthy and free of neurological signs. Definite histopathological changes had occurred as early as four weeks after inoculation, when moderate numbers of bi-nucleated neurons were found within the limbic cortex, striatum, the hypothalamus and amongst the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…It is of utmost interest that as early as 1969, Lampert et al (having cited an earlier article by Arstila et al [88]) suggested that the spongiform change is somehow related to autophagy (84). Those pioneer data were confirmed by Beck et al (89), who also reported membrane lamination observed before full-blown pathology could be appreciated. From examination of the chimpanzee infected with the “K” kuru brain, the typical autophagic vacuoles were illustrated, but the process was not mentioned.…”
Section: Introductionmentioning
confidence: 65%
“…It is of utmost interest that as early as 1969, Lampert et al (having cited an earlier article by Arstila et al [88]) suggested that the spongiform change is somehow related to autophagy (84). Those pioneer data were confirmed by Beck et al (89), who also reported membrane lamination observed before full-blown pathology could be appreciated. From examination of the chimpanzee infected with the “K” kuru brain, the typical autophagic vacuoles were illustrated, but the process was not mentioned.…”
Section: Introductionmentioning
confidence: 65%
“…In the cerebral cortex, the spongiform change and intraneuronal vacuoles were the most prominent lesions, accompanied by a severe astrocytic gliosis. Binucleated neurons were prominent; the same type of neuronal lesions were also seen in the Spider monkey [ 112 ].…”
Section: Transmission Experimentsmentioning
confidence: 91%
“…[ 144 ] and Beck et al . [ 112 ] found severe confluent spongiform change corresponded to typical membrane-bound vacuoles. Neurites showed dystrophic changes.…”
Section: Neuropathologymentioning
confidence: 99%
“…Fusion occurring in vivo between a neuron and a glial cell has been noted electron microscopically in scrapie-infected mouse brain (3). Binucleated neurons occur in brains of patients with kuru (4,5) and in animals with experimental kuru (6,7), and multinucleated cells are commonly seen in cultured tissues from scrapie-infected animals (unpublished data). Together these observations suggested the possibility that the agents of subacute spongiform encephalopathies might promote cell fusion.…”
mentioning
confidence: 81%